Mucuna pruriens Protects against MPTP Intoxicated Neuroinflammation in Parkinson’s Disease through NF-κB/pAKT Signaling Pathways - Rai, Sachchida N.; Birla, Hareram; Singh, Saumitra S.; Zahra, Walia; Patil, Ravishankar R.; Jadhav, Jyoti P.; Gedda, Mallikarjuna R.; Singh, Surya P. (Frontiers in Aging Neuroscience, 2017)
Till date, drugs that have been used to manage Parkinson’s disease (PD) have only shown symptomatic relief with several adverse effects besides their inability to prevent neurodegeneration. Neuroinflammation plays an important role in the advancement of PD and can be targeted for its effective treatment. Researchers have suggested that herbal plants exhibiting the anti-inflammatory and anti-oxidant properties are therefore beneficial to human health. Conventionally, Mucuna pruriens (Mp) seeds are used for maintaining male virility in India. Reportedly, Mp is used as a rejuvenator drug having neuroprotective property. Our study aimed to investigate effects of aqueous extract of Mp (100mg/kgbwt)on neuroinflammation, orally administered to mice intoxicated with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) as well as the molecular mechanism involved in the progression of PD. In this study, we have observed significant behavioural abnormalities beside decreased antioxidant defence in MPTP intoxicated mice. We have also observed significant increase in inflammatory parameters like Glial Fibrillary Acidic Protein, Inducible Nitric Oxide Synthase, Intercellular Cell Adhesion Molecule and Tumor Necrosis Factor alpha in substantia nigra pars compacta (SNpc) of parkinsonian mice. While Mp treatment notably reduced these inflammatory parameters. Mp also inhibited the MPTP induced activation of NF-κB and promoted pAkt1 activity which further prevented the apoptosis of the dopaminergic neurons. Moreover, Mp exhibited significant antioxidant defense by inhibiting the lipids peroxidation and nitrite level, and by improving catalase activity and enhancing GSH level in nigrostriatal region of mouse brain. Mp also recovered the behavioural abnormalities in MPTP treated mice. Additionally, Mp treatment considerably increased the immunoreactivity of Tyrosine Hydroxylase and Dopamine Transporter in SNpc of parkinsonian mice. Our HPLC analysis of these Mp seed extract has shown L-DOPA, gallic acid, phytic acid, quercetin and catechin equivalents as the major components which may cause neuroprotection in PD mice. Our result suggested that Mp extract treatment containing L-DOPA and a mixture of rich novel phytochemicals significantly alleviates the MPTP induced neurotoxicity by NF-κB and pAkt pathway. The findings observed thereby indicate that Mp extract has suggestively ameliorated MPTP induced neuroinflammation, restored the biochemical and behavioral abnormalities in PD mouse and thus provided a scientific basis for its traditional claim.